Analisis Faktor-Faktor yang Mempengaruhi Menurunnya Penerimaan Retribusi Pasar - Salsabila Nur Qatrunnada; Sugih Sutrisno Putra (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Market levies are one of the sources of revenue for Perumda Pasar Juara in Bandung, but there has been a decrease in market retribution receipts in 2020 due to the Covid-19 pandemic. This study aims to determine the effect of PPKM policy, human resource competence, supervision, awareness of mandatory user fees and infrastructure to reduce market retribution revenue in Bandung City. This research is a type of quantitative research with a descriptive approach. The data obtained came from distributing questionnaires to 92 respondents from 46 traders and market officers from 28 traditional markets managed by Perumda Pasar Champion Bandung City. The data analysis method used multiple linear regression analysis using SPSS version 26. The results showed that simultaneously the PPKM policy variables, human resource competence, supervision, awareness of retribution obligations and infrastructure had a positive and significant effect on decreasing market retribution revenue.